Strengthening the Competitiveness of SMEs after the Covid 19 Pandemic (Case Study: Producers of Luti Gendang) - Aulia Agung Dermawan; Muqimuddin Muqimuddin (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Due to the Covid-19 pandemic, many SMEs in Indonesia have been hit hard. Whereas SMEs is a sector that has a major contribution to the Indonesian economy. In addition to the incentives provided by the government for the recovery of SMEs, they are also required to innovate and come up with new strategies in an effort to increase their competitiveness after the Covid 19 Pandemic. To accommodate this, the diamond's porter model was developed as a trigger for formulating strategies to strengthen SMEs competitiveness. The results of the study determine 3 factors of SME competitiveness including production factors, demand conditions factors, and supporting industry factors by 11 indicators. The production factor is the factor with the highest weight (0.4), meaning that it is the most important than the other 2 factors in increasing competitiveness. Of the 30 strategy formulations for SMEs X, there are 2 superior strategies that can be carried out by SMEs X, they are creating customer trust through brand characteristics (0.007) and maintaining consistency in the quality of supply of raw materials in order to produce consistent quality (0.0066). These two strategies can be a concern for SMEs X in increasing its competitiveness Post-Pandemic Covid 19.